University Students’ Knowledge and Attitudes Towards HIV - Houlden, Alexandra Rebecca (2012)
Aim To explore and describe university students’ knowledge of HIV (n=422, a sub-sample of young people), and to test the hypothesis that greater knowledge of HIV/AIDS will be associated with decreased discrimination towards HIV/AIDS. Method Questionnaires were distributed to first year university students studying a variety of subjects. The questionnaire contained both knowledge and attitude questions on the topic of HIV/AIDS. Statistical analysis was completed to understand students’ knowledge levels and attitudes towards the disease, as well as whether there was a correlation between the two. Results 422 students from both arts and science subjects participated in the study. The results showed that as knowledge of HIV increased, attitudes became more positive. However it was also found that some students held positive attitudes despite having poor knowledge on the subject. Knowledge and attitude was not found to vary significantly with age, sex or type of degree, however sexual activity and knowing someone with HIV/AIDS did result in a significant difference in results. Conclusion Overall students’ knowledge of HIV transmission was good, however there were still a worrying number of misconceptions. Students’ knowledge on who has HIV, HIV testing and treatment was poor in many cases. Students attitudes were generally positive, however evidence of discrimination towards HIV/HIV positive individuals was evident. XIII Recommendations HIV health promotion schemes and education programs within schools and universities need to be made more readily available within the UK. These schemes and programs need to highlight not only the transmission routes, testing options and treatments for HIV, but must address the stigma currently surrounding the disease.